"Moral Panics" deflected: the failed legislative response to Canada’s safety crimes and markets fraud legislation - Bittle, Steven (Crime, law and social change, 2011)
This paper critically examines the enforcement, or lack thereof, of criminal laws relating to corporate crime. Using Canada's recently enacted corporate criminal liability (safety crimes) and markets fraud legislation as its empirical focus, it seeks to explain why these laws were introduced, only to fall into a state of virtual disuse. The authors explain how, in the wake of yet another crisis in capitalism, the state felt compelled to enact criminal laws to offset the abuses of corporate power in these two arenas. However, despite promises to 'get tough' on corporate crime, the enforcement of both laws has been sporadic and, in many respects, non-existent. The authors argue that both the passage and the ineffectiveness of Canada's safety crimes and markets fraud legislation can be traced to their shared Keynesian origins as responses to a crisis in neoclassical economics. In essence, both laws are caught-up in a tug-of-war between two opposing yet not incompatible visions of how best to regulate the capitalist marketplace. As a result, even if some corporations and corporate actors are held to legal account, the underlying causes of corporate crime, including the class-based exploitation that is fundamental to capitalism, remain untouched. The authors conclude by arguing for enforcement of corporate crime laws that recognizes the limits of this struggle and the necessity to stave-off capitalism's endemic harms.